Simultaneous determination of two plant growth regulators in ten food samples using ion chromatography combined with QuEChERS extraction method (IC-QuEChERS) and coupled with fluorescence detector. (15th February 2018) - Muhammad, Nadeem; Subhani, Qamar; Wang, Fenglian; Lou, Chaoyan; Liu, Junwei; Zhu, Yan
Highlights: A simple and highly sensitive isocratic IC-FLD method was developed for analysis of similar PGRs. A new modified and miniaturized IC-QuEChERS method was optimized using PS-DVB as a sorbent. Validated results were acceptable for both analytes in all ten food samples. Matrix effects and sensitivity problems were solved by using IC-QuEChERS and IC-FLD technique. Abstract: A new simple, isocratic, selective and highly sensitive method has been developed for the simultaneous separation and determination of two plant growth regulators (PGRs): 2-(1-Naphthyl)acetic acid (NAA) and 2-(Naphthalen-1-yl)acetamide (NAD). Both PGRs were extracted by modified and miniaturized ion chromatography-Quick, Easy, Cheap, Effective, Rugged and Safe (IC-QuEChERS) method from ten food samples. The separation and sensitive determination were carried out by using ion chromatography coupled with fluorescence and ultraviolet (IC-FLD/UV) detector. The proposed analytical and extraction methods were validated by using blank samples, fortified with a standard solution of these two PGRs at three concentration levels 5, 15 and 25 µg/kg. The method showed good linearity (r 2  ≥ 0.980), satisfactory recoveries (76.3–112) with tolerable precision having relative standard deviations less than 15.4% (RSDs, n = 3). The limit of detection and limit of quantification were also in the range of 0.08–6.6 ng/kg and 2.2–20 ng/kg, respectively.